Perbandingan notasi pertandingan bulutangkis nomor tunggal putra pada olimpiade Rio 2016 dan Beijing 2020 - Kusuma, Angga Indra; BP, Ismawandi; Utamayasa, I Gede Dharma; Sari, Marthinna Ratna; Anggraeni, Dwi Cahyati (Universitas Hamzanwadi, 2023)
This research aims to compare the match notations between the men's singles matches in Rio 2016 and Rio 2020. It is urgent to discuss this matter because the Olympics is a routine event held every 4 years, to prepare for the next Olympics, team officials can evaluate the Rio match resume. 2016 and Tokyo 2020. This research is classified as quantitative research and the method used is audiovisual analysis. The sample for this research is the men's singles final match for badminton) at the 2016 Rio and 2020 Beijing Olympics. Data collection procedures, data were obtained from the IOC (international Olympic Committee's) website. The spreadsheet used to collect data was using a spreadsheet in the Excel 2019 application. Data analysis was used, namely the difference test with the help of SPSS 21. The results of the research obtained a description of the hitting techniques carried out up to the rally and rest times as well as comparisons. The conclusion obtained is that there is a difference between rally time and rest time between the Rio 2016 and Tokyo 2020 matches.